Fast Channel Navigation of Internet Protocol Television Using Adaptive Hybrid Delivery Method - Timothy T. Adeliyi; Oludayo O. Olugbara (Journal of Computer Networks and Communications)
The Internet protocol television brought seamless potential that has revolutionized the media and telecommunication industries by providing a platform for transmitting digitized television services. However, zapping delay is a critical factor that affects the quality of experience in the Internet protocol television. This problem is intrinsically caused by command processing time, network delay, jitter, buffer delay, and video decoding delay. The overarching objective of this paper is to use a hybrid delivery method that agglutinates multicast- and unicast-enabled services over a converged network to minimize zapping delay to the bare minimum. The hybrid method will deliver Internet protocol television channels to subscribers using the unicast stream coupled with differentiated service quality of experience when zapping delay is greater than 0.43 s. This aids a faster transmission by sending a join message to the multicast stream at the service provider zone to acquire the requested channel. The hybrid method reported in this paper is benchmarked with the state-of-the-art multicast stream and unicast stream methods. Results show that the hybrid method has an excellent performance by lowering point-to-point queuing delay, end-to-end packet delay, and packet variation and increasing throughput rate.